Development of Axial Continuous Metal Expeller for Melt Conditioning of Alloys - Cassinath, Z.; A. K., Prasada Rao (IOP Publishing, 2016)
ACME (Axial, centrifugal metal expeller) is a novel processing technology developed independently for conditioning liquid metal prior to solidification processing. The ACME process is based on an axial compressor and uses a rotor stator mechanism to impose a high shear rate and a high intensity of turbulence to the liquid metal, so that the conditioned liquid metal has uniform temperature and uniform chemical composition as it is expelled. The microstructural refinement is achieved through the process of dendrite fragmentation while taking advantage of the thixotropic property of semisolid metal slurry so that it can be conveyed for further downstream operations. This paper introduces the concept and its advantages over current technologies.